2004
DOI: 10.1111/j.1475-6811.2004.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Romantic involvement and depressive symptoms in early and late adolescence: The role of a preoccupied relational style

Abstract: Two studies examined the association between depressive symptoms and romantic involvement in adolescence and tested the hypothesis that romantic involvement is associated more strongly with symptoms among adolescents who have a more preoccupied style of relating, compared to adolescents who have a less preoccupied style of relating. Study 1 (N = 96 early adolescent females) examined concurrent associations and Study 2 (N = 80 late adolescent males and females) examined longitudinal associations. In both age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
129
3
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 42 publications
12
129
3
6
Order By: Relevance
“…Like co-rumination, romantic experiences are associated with adolescent depression (Davila, Steinberg, Kachadourian, Cobb, & Fincham, 2004;Joyner & Udry, 2000). Given the developmental salience of romantic experiences in early adolescence and the importance of peer influence on the formation of early romantic relationships (Brown, 1999;Connolly & Goldberg, 1999), it seems likely that co-ruminating teens would often discuss problems associated with romantic desires, experiences, and failures.…”
Section: Relation To Romantic Experiencesmentioning
confidence: 99%
“…Like co-rumination, romantic experiences are associated with adolescent depression (Davila, Steinberg, Kachadourian, Cobb, & Fincham, 2004;Joyner & Udry, 2000). Given the developmental salience of romantic experiences in early adolescence and the importance of peer influence on the formation of early romantic relationships (Brown, 1999;Connolly & Goldberg, 1999), it seems likely that co-ruminating teens would often discuss problems associated with romantic desires, experiences, and failures.…”
Section: Relation To Romantic Experiencesmentioning
confidence: 99%
“…Although the bulk of this evidence comes from studies of adults, Collins et al (2002) successfully used a similar measure (the Hazan and Shaver three-paragraph measure; Hazan and Shaver, 1987) with a large sample of adolescents. Furthermore, our own data set demonstrates preliminary psychometric properties for the RQ in an adolescent sample (Davila et al, 2004).…”
Section: Attachment Securitymentioning
confidence: 99%
“…Past research identified adolescent romantic involvement as an important correlate of depressive symptoms (e.g., Davila et al, 2004;Joyner & Udry, 2000;Larson et al, 1999;Monroe et al, 1999). Overall, findings from these studies reveal that adolescents involved in a romantic relationship and/or are steady or frequent daters report more depressive symptoms than adolescents not romantically involved and/or are not steady or frequent daters.…”
Section: Associations Between Adolescent Romantic Involvement Adolessupporting
confidence: 50%
“…These experiences can challenge adolescents' coping skills and self-concepts, particularly among adolescent girls who begin to date early (i.e., before age 14) or who date frequently (e.g., Carlson & Rose, 2007;Davies & Windle, 2000;Davila, 2007;Davila, Steinberg, Kachadourian, Cobb, & Fincham, 2004;Joyner & Udry, 2000;Larson & Asmussen, 1991;Monroe, Rhode, Seeley, & Lewinsohn, 1999;Quatman, Sampson, Robinson, & Watson, 2001). For example, in a cross-sectional study of early-adolescent girls (N = 96; mean age = 13.24 years), Davila et al (2004) found that girls who reported current or past involvement in a romantic relationship reported greater depressive symptoms than girls with no romantic involvement. Monroe et al (1999) found that thinking about relationship disturbances was linked to depressed mood, especially among girls.…”
Section: Stressors and Challenges Relating To Romantic And Sexual Intmentioning
confidence: 99%